2021
DOI: 10.5194/acp-21-4939-2021
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variation, sources, and secondary transformation potential of volatile organic compounds in Xi'an, China

Abstract: Abstract. As critical precursors of ozone (O3) and secondary organic aerosols, volatile organic compounds (VOCs) play a vital role in air quality, human health, and climate change. In this study, a campaign of comprehensive field observations and VOC grid sampling was conducted in Xi'an, China, from 20 June to 20 July 2019 to identify the spatiotemporal concentration levels, sources, and secondary transformation potential of VOCs. During the observation period, the average VOC concentrations at the Chanba (CB)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 86 publications
1
36
0
Order By: Relevance
“…However, there are differences in the sources that contribute to VOC emission across regions in China. In the cities of Langfang and Xiamen, paint solvents constitute the highest contributing factor to VOC emission (62), while vehicular exhaust and combustion are the primary sources of VOCs in Wuhan City (63). In another study (59), it was reported that about 40 VOCs were observed in more than 50% of air samples collected from residences of pregnant women in Northeastern British Columbia, a region of natural gas exploitation, while four VOCs were detected in more than 50% of the water samples tested.…”
Section: Anthropogenic Sourcesmentioning
confidence: 99%
“…However, there are differences in the sources that contribute to VOC emission across regions in China. In the cities of Langfang and Xiamen, paint solvents constitute the highest contributing factor to VOC emission (62), while vehicular exhaust and combustion are the primary sources of VOCs in Wuhan City (63). In another study (59), it was reported that about 40 VOCs were observed in more than 50% of air samples collected from residences of pregnant women in Northeastern British Columbia, a region of natural gas exploitation, while four VOCs were detected in more than 50% of the water samples tested.…”
Section: Anthropogenic Sourcesmentioning
confidence: 99%
“…The great changes in the mixing ratios of different species are mainly affected by photochemical processing, emission inputs, and ratios of VOC species having similar atmospheric lifetimes can reflect the source features (B. Li et al, 2019;Raysoni et al, 2017;Song et al, 2021). The ratio of ipentane to n-pentane is widely used to examine the impact of vehicle emissions, fuel evaporation, and combustion emissions within the i/n-pentane ratios of ranging 2.…”
Section: Indication From Tracersmentioning
confidence: 99%
“…During the clean day, both of the distributions show large spatial variabilities with high CV values ( hot spots for benzene and toluene are not the same, highlighting the difference in emissions from individual vehicles (Mo et al, 2016). The toluene-to-benzene concentration ratio (T/B) is widely used to differentiate the VOC sources (Song et al, 2021; and references therein). According to literature, traffic emissions have T/B ratios from 1 to 3 depending on vehicle type and fuel composition.…”
Section: Spatial Distribution Of Gaseous Pollutantsmentioning
confidence: 99%
“…Moreover, grid sampling and simultaneous measurements at multiple sites are often used to investigate the spatial variations of air pollutants on sparse spatial scales. Previous studies show that the surface concentrations of VOCs and PM2.5 components vary because of different source contributions in metropolitan areas in China (Chen et al, 2020;Song et al, 2021).…”
Section: Introductionmentioning
confidence: 99%